Microinjection molding simulation of a microfluidic device - Su, Xiangyong (2014)
Fabrication of high quality micro-structures in polymeric microfluidic devices using microinjection molding is particularly challenging. The need to achieve fine features with small dimensions and high aspect ratios in these microstructures makes it difficult to optimize the molding process. Simulation is a technique that has been widely used to predict the performance of injection molding. However, studies on simulation of microinjection molding using commercial software packages are lacking. In this project, a simulation model of the injection mold filling process for a microfluidic device has been created. Analyses of predicted molding behaviors suggest a design change in the orientation and location of microfeatures that could bring about improvements in molded microfeatures quality. Similarities and discrepancies between simulated results and actual molded parts have also been addressed. This investigation has led to a better understanding in the molding performance for a microfluidic device design and possible improvements in the creation of a microinjection molding simulation.